Analysis of wheat microspore embryogenesis induction by transcriptome and small RNA sequencing using the highly responsive cultivar "Svilena". Issue 1 (December 2016) - Seifert, Felix; Bössow, Sandra; Kumlehn, Jochen; Gnad, Heike; Scholten, Stefan
Abstract Background Microspore embryogenesis describes a stress-induced reprogramming of immature male plant gametophytes to develop into embryo-like structures, which can be regenerated into doubled haploid plants after whole genome reduplication. This mechanism is of high interest for both research as well as plant breeding. The objective of this study was to characterize transcriptional changes and regulatory relationships in early stages of cold stress-induced wheat microspore embryogenesis by transcriptome and small RNA sequencing using a highly responsive cultivar. Results Transcriptome and small RNA sequencing was performed in a staged time-course to analyze wheat microspore embryogenesis induction. The analyzed stages were freshly harvested, untreated uninucleate microspores and the two following stages fromin vitro anther culture: directly after induction by cold-stress treatment and microspores undergoing the first nuclear divisions. Ade novo transcriptome assembly resulted in 29, 388 contigs distributing to 20, 224 putative transcripts of which 9, 305 are not covered by public wheat cDNAs. Differentially expressed transcripts and small RNAs were identified for the stage transitions highlighting various processes as well as specific genes to be involved in microspore embryogenesis induction. Conclusion This study establishes a comprehensive functional genomics resource for wheat microspore embryogenesis induction and initial understanding of molecular mechanisms involved. A large set of putative transcripts presumably specific for microspore embryogenesis induction as well as contributing processes and specific genes were identified. The results allow for a first insight in regulatory roles of small RNAs in the reprogramming of microspores towards an embryogenic cell fate.